Redução de custos com internações por doenças respiratórias por meio da produção de biodiesel obtido com óleo de fritura residual: survey na cidade de São Paulo - Miranda, Amanda Carvalho (2018)
Pollutants emission by diesel cycle vehicles increasingly affects air quality in the city of São Paulo. This factor directly contributes to the increase of hospitalizations due to respiratory diseases. The present study studied the cases of hospitalizations due to respiratory diseases and their costs, caused by these pollutants, in the period from 2008 to 2017, in the city of São Paulo; these data were collected on the DATA-SUS website, both correlated with the air quality standards established by CONAMA (National Environmental Council) by CETESB and WHO. The work also proposed the selective collection of residual frying oils made in the city of São Paulo, to convert it into Biodiesel as an economic, environmental and social alternative. It was elaborated a questionnaire, distributed in 600 restaurates and 1500 residences of the city of São Paulo, with the purpose of estimating the consumption of oil of monthly fryings of these establishments, as well as to establish the level of knowledge of the population on the discard of these residues. The results pointed out that the city of São Paulo has potential biodiesel production through residual oils of more than 8,800 m3 per month, making possible a gain from the sale of excess biodiesel of US $ 1,056 million, in addition to profit with its by-product Glycerin $ 5.089 billion and $ 0.166 million in carbon credit sales. The results of the pollutants showed that the Particulate Material (MP10), (MP2.5) and Ozone (O3) presented a moderate to bad correlation, mainly in months with low precipitation, corroborating with an increase in hospitalizations due to systemic diseases during the same period; the costs with these externalities reached a total of R $ 442.7 million by the SUS. It was concluded that the replacement of diesel by Biodisel of residual oils in the bus fleet in the city of São Paulo would be a viable alternative, would eliminate the emission of pollutants by 30%, providing a reduction of costs with hospital admissions by the SUS in the period of 2008 to 2017 of more than R $ 126.8 million, in addition to recovering the image of the city with sustainable initiatives and improvements in the quality of life of its population.